ADSORPTION CHARACTERISTIC OF IRON ONTO POLY[EUGENOL-CO-(DIVINYL BENZENE)] FROM AQUEOUS SOLUTION - Fitrilia Silvianti; Dwi Siswanta; Nurul Hidayat Aprilita; Agung Abadi Kiswandono (Universitas Syiah Kuala, 2017)
A study on the adsorption characteristic of Iron onto Poly[eugenol-co-(divinyl benzene)] (EDVB) from aqueous solution has been conducted. EDVB was produced and characterized by using FTIR spectroscopy. The adsorption was studied by a batch method by considering the factors affecting the adsorption such as initial metal ion concentration, adsorption selectivity, and mechanism of adsorption using a sequential desorption method. The adsorption of Iron onto EDVB followed a pseudo-2 order kinetics model with the rate constant of 0,144 L2 mmol-1 min-1. The adsorption isotherm was studied with Tempkin, Langmuir and Freundlich models. The adsorption capacity (Qmax) obtained by Langmuir isotherms was 250mg.L-1 while the equilibrium value was 0.8 Lmg-1. A competitive adsorption study showed that EDVB is adsorbed selectively towards Iron rather than Chromium, Coppers and Cadmium ions. The interaction type of Iron onto EDVB was determined by a sequential desorption.Keywords: Polyeugenol; divinyl benzene (DVB); adsorption; Iron; FeReferencesAbasi, C. Y.; Abia, A.A.; Igwe, J.C. Adsorption of Iron (III), Lead (II) and Cadmium (II) Ions by Unmodified Raphia Palm (Raphia hookeri) Fruit Endocarp. Environ. Res. 2011, 5 (3), 104-113, ISSN: 1994-5396, Medwell Journals. DOI: 10.3923/erj.2011.104.113Baes, F. C.; Mesmer, R. E. The Hydrolisis of Cations; John Wiley: New York, 1976Bakatula, E.N.; Cukrowska, E.M.; Weiersbye, L.; Mihali-Cozmuta, L.;Tutu, H. Removal of toxic elements from aqueous solution using bentonite modified with L-histidine. Water Sci. Technol.2014, 70 (12),2022-2030, DOI: 10.2166/wst.2014.450Bhattacharyya, K.G.; Gupta, S.S. Adsorption of Fe(III) from Water by Natural and Acid Activated Clays: Studies on equilibrium isotherm, kinetics and thermodynamics of interactions. Adsorption. 2006, 12 (3), 185-204,DOI : 10.1007/s10450-006-0145-0Carmona, M..; Lucas, A.D.; Valverde, J.L.; Velasco, B.; Rodriguez, J.F. Combined adsorption and ion exchange equilibrium of phenol on Amberlite IRA-420.Chem. Eng. J.2006, 117, 155-160, Doi : 10.1016/j.cej.2005.12.013Debnath, S.; Ghosh, U.C. Kinetics, isotherm and thermodynamics for Cr(III) and Cr(VI) adsorption from aqueous solutions by crystalline hydrous titanium oxide. J. Chem. Thermodin. 2008, 40: 67-77, DOI: 10.1016/j.jct.2007.05.014Djunaidi, M.C.; Jumina; Siswanta, D.; Ulbricht, M. Selective Transport of Fe(III) Using Polyeugenol as Functional Polymer with Ionic Imprinted Polymer Membrane Method. Asian J. Chem. 2015, 27 (12): 4553-4562, DOI : 10.14233/ajchem.2015.19228Febriasari, A.; Siswanta, D.; Kiswandono, A.A.; Aprilita, N.H. Evaluation of Phenol Transport Using Polymer Inclusion Membrane (PIM) with Polyeugenol as a Carrier. Jurnal Rekayasa Kimia dan Lingkungan. 2016, Vol. 11, No. 2, 99-106, DOI: 10.23955/rkl.v11i2.5112Foldesova, M.; Dillinger, P.; Luckac, P. Sorption and Desorption of Fe(III) on Natural and chemically modified zeolite. J. Radioanal. Nucl. Chem. 1999, Vol. 242, No. 1 (1999), 227-230, DOI: 10.1007/BF02345926Gupta, V.K.;Sharma, S. Removal of cadmium and zinc from aqueous solutions using mud.Environ. Sci. Technol. 2002, 36: 3612-3617, DOI: 10.1021/es020010vHandayani, D.S. Sintesis kopoli(eugenol-DVB) sulfonat dari Eugenol Komponen Utama Minyak Cengkeh Szygium aromaticum (Synthesis of copoly(eugenol-DVB) sulfonic from main components of eugenol clove oil Szygium aromaticum). Biopharmacy Journal of Pharmacological and Biological Sciences. 2004, 2 (2): 53-57 ISSN: 1693-2242. url : https://eprints.uns.ac.id/id/eprint/856Harimu, L.; Matsjeh, S.; Siswanta, D.; Santosa, S.J. Synthesis of Polyeugenyl Oxyacetic Acid as Carrier to Separate Heavy Metal Ion Fe(III), Cr(III), Cu(II), Ni(II), Co(II), and Pb(II) that Using Solvent Extraction Mehod. Indo. J. Chem. 2009, 9 (2): 261-266.Ho, Y.S.; McKay, G. Pseudo-second Order Model for Sorption Processes. Process. Biochem. 1999, 34, 451-465, DOI: 10.1016/S0032-9592(98)00112-5Ho, Y.S.; McKay, G.; Wase, D.A.J.;Forster, C.F. Study of Sorption Divalent Metal Ions on to Peat. Adsorpt. Sci. Technol. 2000, 18: 639-650. DOI : 10.1260/0263617001493693Indah, S.; Helard, D.;Sasmita, A. Utilization of maize husk (Zea mays L.) as low-cost adsorbent in removal of iron from aqueous solution. Water Sci. Technol. 2016, 73 (12), 2929-2935, DOI: 10.2166/wst.2016.154Kiswandono, A.A.; Siswanta, D.; Aprilita, N.H.; Santosa, S.J. Transport of Phenol through inclusion polymer membrane (PIM) using copoly(Eugenol-DVB) as membrane carries. Indo .J. Chem. 2012, 12 (2): 105-112. Doi : 10.22146/ijc.667Kousalya, N.; Gandhi, M.R.; Sundaram, C.S.; Meenakshi, S. Synthesis of nano-hydroxyapatite chitin/chitosan hybrid bio-composites for the removal of Fe(III).Carbohyd. Polym. 2010, 82: 594-599, DOI:10.1016/j.carbpol.2010.05.013Kumar, K.V.; Porkodi, K.;Rocha, F. Langmuir-Hinshelwood kinetics – A theoretical study, Catalysis Communications. 2008, 9: 82-84, DOI:10.1016/j.catcom.2007.05.019Masel, R.I. Principles Adsorption and Reaction on Solid Surface; John Wiley Sons: Canada, 1996Moore, J. W.; Pearson, R.G. Kinetics and Mechanism Third Edition; John Wiley Sons: Canada, 1981.Ngah, W.S.W.; Ghani, S.A.; Kamari, A. Adsorption Behaviour of Fe(II) and Fe(III) Ions in Aqueous Solution on Chitosan and Cross-linked Chitosan Beads. Bioresource. Technol. 2005, 96: 443-450. DOI:10.1016/j.biortech.2004.05.022Rahim, E.A.; Sanda, F.; Masuda, T. Synthesis and Properties of Novel Eugenol-Based Polymers. Polymer Bulletin. 2004, Vol. 5, 93-100, DOI: 10.1007/s00289-004-0272-2Samarghandi, M.R.; Hadi. M.; Moayedi, M.; Askari, F.B. 2009. Two Parameter Isotherms of Methyl Orange Sorption by Pinecone Derived Activated Carbon. Iran. J. Environ. Health Sci. Eng., 6 (4): 285-294.Setyowati, L. 1998. Pengaruh Penambahan Divinil Benzena (DVB) pada Kopolimerisasi Kationik Poli[eugenol-co-(divinil benzena)] dan Sifat Pertukaran Kation Kopoligaramnya (The Effect of divinylbenzene (DVB) Addition to Eugenol-DVB Cationic Copolymerization and Its Use As Cation-Exchanger), Thesis, Faculty of Mathematics and Natural Sciences, Universitas Gadjah Mada, Yogyakarta, Indonesia.Shi, T.; Jia, S.; Chen, Y.; Wen, Y.; Du, C.; Guo, H.; Wang, Z. Adsorption of Pb(II), Cr(III), Cu(II), Cd(II) and Ni(II) onto a vanadium mine tailing from aqueous solution. J. Hazard. Mater. 2009, 169: 838-846, DOI: 10.1016/j.jhazmat.2009.04.020Sun, S.;Wang, A. Adsorption Kinetics of Cu(II) Ions Using N,O-Carboxymethyl-Chitosan. J. Hazard. Mater. 2006, B131: 103-111, DOI: 10.1016/j.jhazmat.2005.09.012Sun, S.; Wang, L.;Wang, A. Adsorption Properties of Crosslinked Carboxymethyl-chitosan Resin With Pb(II) as Template Ions. J. Hazard. Mater. 2006, B136: 930-937, DOI: 10.1016/j.jhazmat.2006.01.033Uzun, I.; Guzel, F. Adsorption of Some Heavy Metal Ions from Aqueous Solution by Activated Carbon and Comparison of Percent Adsorption Result of Activated Carbon with those of Some Other Adsorbents. Turk. J. Chem. 2000, 24: 291-297.Zou, X.; Pan, J.; Ou, H.; Wang, X.;Guan, W.; Li, C.; Yan, Y.; Duan, Y. Adsorptive removal of Cr(III) and Fe(III) from aqueous solution by chitosan/attapulgite composites: Equilibrium, thermodynamics and kinetics. Chem. Eng. J. 2011, 167: 112-121, DOI: 10.1016/j.cej.2010.12.009